FEASIBILITY ANALYSIS OF OIL PALM FARMING IN RESPONSE TO CHANGES IN FRESH FRUIT BUNCH (FFB) PRICES IN MABAR VILLAGE, BANGUN PURBA DISTRICT, DELI SERDANG REGENCY - Sanggam Simanjuntak; Pebri Yunus Nababan; Saprida (Prodi Agribisnis Fakultas Agro Teknologi Universitas Prima Indonesia, 2026)
Oil palm is one of the most important plantation commodities contributing significantly to national economic development and rural livelihoods. For smallholder farmers, oil palm serves as a primary source of income whose sustainability is strongly influenced by fluctuations in Fresh Fruit Bunch (FFB) prices. Changes in FFB prices over recent years have affected farmers’ ability to maintain and manage their farming activities. This study aimed to analyze the feasibility of oil palm farming in relation to changes in FFB prices in Mabar Village, Bangun Purba District, Deli Serdang Regency. The research employed a survey method with a descriptive quantitative approach. The study area was purposively selected because it represents one of the major smallholder oil palm production centers in Deli Serdang Regency. A total of 60 farmers were selected as respondents from a population of 150 farmers using the Slovin formula. Data were collected through observation, interviews, and documentation and analyzed descriptively. The results indicate that most farmers are within productive age groups, possess considerable farming experience, and manage small- to medium-scale plantations. Changes in FFB prices influence plantation management activities and farmers’ business decisions. Despite price fluctuations, farmers continue cultivating oil palm because it remains an important source of livelihood. Therefore, oil palm farming in Mabar Village remains feasible and continues to offer promising prospects for smallholder farmers.